2011
DOI: 10.1245/s10434-011-1876-z
|View full text |Cite
|
Sign up to set email alerts
|

Unplanned Excision of Soft Tissue Sarcoma Results in Increased Rates of Local Recurrence Despite Full Further Oncological Treatment

Abstract: Unplanned initial excision of extremity soft tissue sarcoma may compromise long-term local control of extremity STS despite full further oncological management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 21 publications
3
85
1
6
Order By: Relevance
“…[8][9][10] Despite the present study not demonstrating a significant association between residual tumor and LR, other groups have reported that initial unplanned ESTS resection and residual disease predicted LR. 8,9 In a study of 142 unplanned ESTS resections from Charoenlap, the amputation rate was significantly higher in patients with residual disease (18.5 vs. 1.8 %, p = 0.003). Of note, only 10 % of patients in the Charoenlap study had leiomyosarcoma compared with 22 % in the report from Bonvalot.…”
contrasting
confidence: 94%
“…[8][9][10] Despite the present study not demonstrating a significant association between residual tumor and LR, other groups have reported that initial unplanned ESTS resection and residual disease predicted LR. 8,9 In a study of 142 unplanned ESTS resections from Charoenlap, the amputation rate was significantly higher in patients with residual disease (18.5 vs. 1.8 %, p = 0.003). Of note, only 10 % of patients in the Charoenlap study had leiomyosarcoma compared with 22 % in the report from Bonvalot.…”
contrasting
confidence: 94%
“…Local recurrence rates in such patients are significantly higher than those undergoing a planned wide excision, even following re-excisions and radiotherapy. 18 The decision to excise an elastofibroma should be made jointly by the patient and surgeon. In the absence of significant symptoms, there is no benefit in removing these lesions, and non-operative management should be pursued.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor biopsies that are done incorrectly often compromise the chance of local control, may complicate reconstructive procedures, and have been shown to increase the rate of local recurrence. 20 If the biopsy is not performed at a medical center with expertise in treating osteosarcoma, there is a greater likelihood of biopsy-associated complications, such as obtaining non-diagnostic tissue, hematoma, infection, and pathologic fracture. 21,22 Histological Evaluation OS cells are of mesenchymal origin and are histologically characterized by the abnormal production of osteoid.…”
Section: Os Biopsymentioning
confidence: 99%